Career risk and market discipline in asset management - Andrew Ellul; Marco Pagano; Annalisa Scognamiglio (Goethe University Frankfurt, Center for Financial Studies (CFS), 2018)
We establish that the labor market helps discipline asset managers via the impact of fund liquidations on their careers. Using hand-collected data on 1,948 professionals, we find that top managers working for funds liquidated after persistently poor relative performance suffer demotion coupled with a significant loss in imputed compensation. Scarring effects are absent when liquidations are preceded by normal relative performance or involve mid-level employees. Seen through the lens of a model with moral hazard and adverse selection, these results can be ascribed to reputation loss rather than bad luck. The findings suggest that performance-induced liquidations supplement compensation-based incentives.
urn:nbn:de:hebis:30:3-473495
Keywords: G20; G23; J24; J62; J63; 330; careers; hedge funds; asset managers; market discipline; scarring effects